Detection of Mycoplasma spp. from snakes from five different families - Marline M. Faulhaber; Florence Tardy; Franziska Saul; Elisabeth Müller; Michael Pees; Rachel E. Marschang (BMC Veterinary Research)
Abstract Background Mycoplasmas are an important cause of respiratory diseases in tortoises. In snakes, evidence of mycoplasma infections has been found almost exclusively in pythons. To better understand the occurrence of these bacteria in other snake species, samples submitted for routine testing for respiratory pathogens were also tested for mycoplasma by polymerase chain reaction (PCR). A total of 640 samples (mostly oral swabs) from snakes of 5 different families (Boidae n = 114, Colubridae n = 109, Elapidae n = 34, Pythonidae n = 301 and Viperidae n = 82) were included in the study. A genus-specific PCR (PCR1) developed for the detection of Mycoplasma [Mycoplasmopsis] agassizii and a pan-mycoplasma PCR (PCR2) were used. PCR products were sequenced for validation and phylogenetic analysis was performed. The sampled animals were from various owners and collections, all in human care at the time of sampling. Clinical background information was not provided. Results Using PCR1, mycoplasmas were detected in 175 (175/640, 27%) samples (Boidae: 7/114, 6%; Colubridae: 3/109, 3%; Elapidae: 8/34, 24%; Pythonidae: 155/301, 51%; Viperidae: 2/82, 2%). A higher percentage of positive results were obtained using PCR2 (258/640, 40%; Boidae: 9/114, 8%; Colubridae: 25/109, 23%; Elapidae: 19/34, 56%; Pythonidae: 172/301, 57%; Viperidae: 33/82, 40%). The detected bacteria can be divided into at least 6 genetically diverse clusters representing different genera and species based on multiple sequence alignment and phylogenetic analysis. Conclusions These results show that diverse mycoplasmas are found in pythons and other snakes. Further investigations are necessary to evaluate the role of various mycoplasmas in respiratory diseases in snakes.